Bridging the gap: glucose transporters, Alzheimer’s, and future therapeutic prospects - Albaik, Mai; Sheikh Saleh, Dalaa; Kauther, Dana; Mohammed, Hajira; Alfarra, Shurouq; Alghamdi, Adel; Ghaboura, Nehmat; Sindi, Ikhlas A. (Frontiers in Cell and Developmental Biology, 2024)
Glucose is the major source of chemical energy for cell functions in living organisms. The aim of this mini-review is to provide a clearer and simpler picture of the fundamentals of glucose transporters as well as the relationship of these transporters to Alzheimer's disease. This study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Electronic databases (PubMed and ScienceDirect) were used to search for relevant studies mainly published during the period 2018-2023. This mini-review covers the two main types of glucose transporters, facilitated glucose transporters (GLUTs) and sodium-glucose linked transporters (SGLTs). The main difference between these two types is that the first type works through passive transport across the glucose concentration gradient.The second type works through active co-transportation to transport glucose against its chemical gradient. Fluctuation in glucose transporters translates into a disturbance of normal functioning, such as Alzheimer's disease, which may be caused by a significant downregulation of GLUTs most closely associated with insulin resistance in the brain. The first sign of Alzheimer's is a lack of GLUT4 translocation. The second sign is tau hyperphosphorylation, which is caused by GLUT1 and 3 being strongly upregulated. The current study focuses on the use of glucose transporters in treating diseases because of their proven therapeutic potential. Despite this, studies remain insufficient and inconclusive due to the complex and intertwined nature of glucose transport processes. This study recommends further understanding of the mechanisms related to these vectors for promising future therapies.